Streptococcus milleri and Recurrent Intra-Abdominal Abscesses: A Case Report and Literature Review - Tabitha M. Gana; Olugbenga Awolaran; Sobia Akhtar (Case Reports in Surgery)
We report a case of recurrent intra-abdominal abscesses as a postoperative complication following diverticular perforation in which Streptococcus milleri (SM) was isolated. SM is evaluated here as a potent pyogenic organism commonly associated with intra-abdominal abscess especially in the postoperative setting. With the commonly adopted conservative management, the challenges of recurrence and prolonged hospital stay experienced in the indexed case as well as many other previous reports are highlighted. We also present a recommendation of the need for a more intensive approach of SM-related abscess drainage along with areas that would benefit further research.